Factors influencing employee engagement at Selangor state health department (JKNS) / Nurul Izzah Muhamad Arif , Noral Elissa Ahmad Latffi and Farid Nazrin Md. Hafiz - Muhamad Arif, Nurul Izzah; Ahmad Latffi, Noral Elissa; Md. Hafiz, Farid Nazrin (Arshad Ayub Graduate Business School, 2018)
Employee engagement is emerging as a vital organizational issue especially as businesses are drastically recovering from the trauma of the global recession. There is a need for academic research on the construct to ascertain the claims of the human resource consulting firms as well as to add to the existing knowledge of employee engagement in the literature Employee in the private and government sectors both are likely to have less engagement to the organization. This study was conducted based on The Gallup News that reported only 12% of employees in Asia are engaged at work Crabtree (2013). Despite that, there were no evidence of a study conducted on employee engagement at Jabatan Kesihatan Negeri Selangor (JKNS). Thus, leading towards this study conducted to gain insights on the level of employee engagement at JKNS. This study was conducted on a population of 500 employees working in JKNS with the purpose of identifying significant factors and gauging the level of employee engagement within the department using the measures of employee engagement (Pride, Advocacy, Attachment, Inspiration and Motivation) as the variables. Data was gathered through interview and surveys at JKNS. The mean, standard deviation, skewness, Cronbach’s Alpha, Pearson Correlation, and Multiple Regression were used for data analysis. Findings of the study showed significant relationship between all five variables towards the employee engagement at JKNS. To no avail, this study was limited to the cooperation from respondents, gender disparity, time constraint and the confidentiality of government data. This study contributes to the relationship between employee engagement at JKNS as a government agency and the outcome of this research would support as insights to the Management in decision making towards organizational performance. Within this study, few recommendations were drawn such as organization should enhance the sense of pride among employees, boosting the motivation level of employees and to adopt best practice in human resource.